Pariwisata Ekonomi Kreatif Dalam Upaya Menarik Minat Wisatawan dan Meningkatkan Kesejahteraan Masyarakat Destinasi Pariwisata (Studi Kasus Saung Angklung Udjo) - Setiawan, Christin; Hidayat, Candra; Gantina, Devita (Jurnal Ilmiah Pariwisata, 2021)
The purpose of this study is to determine the pre-existing forms of creativity that the community will undertake and identify ways to increase community income. The method used is a quantitative descriptive approach by taking a sample of 125 people from 650 existing populations. The results showed that the price sold by Saung Angklung Udjo with the indication that was presented based on the brochure was directly proportional, namely good. The performance of Saung angklung Udjo slightly reduces the sacred value in Sundanese culture because it changes its function to become a commercial performance. The emergence of Saung Angklung Udjo influenced the emotional motives of the millennial generation who were satisfied and happy with the appearance of Saung Angklung Udjo, thereby increasing the attractiveness of creative tourism. The Saung Angklung Udjo demonstration can provide investment opportunities, such as setting up a restaurant and a gift shop. Keywords: Creativity; Tourists; Income